CAREER DEVELOPMENT EFFECT ON EMPLOYEE PERFORMANCE IMPROVEMENT - Santoso, Anton Budi; Oktafien, Shinta; Roespinoedji, Djoko; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this research is to find out how much influence career development factors have on improving employee performance at PT. XYZ. The population in this study are employees who work in this company, especially in the Warehouse Finish Good (FG), Warehouse Raw Material & Packaging Material (RMPM), Quality Assurance (QA), and Production and Engineering sections, totalling 327 people with the number of samples taken as many as 180 respondents. The research method used is in the form of causal associative research which aims to analysis the relationship between one variable and another or how one variable can affect or be influenced by other variables. Meanwhile, for the calculation of data processing and analysis using simple linear regression analysis which is calculated with the help of SPSS software version 20.0. With reference to the research results obtained, it is known that career development has a significant influence on improving employee performance. Thus, it is concluded that the higher the position that can be occupied by an employee while working at an organization or company, the better the work results shown by the employee. This is due to the sense of pride possessed by the employee when he is able to get the opportunity to occupy a higher position which results in higher morale.